Assessment of motor behavior and motion preíndices goalkeeper during penalty shot - F. J. Núñez (European Journal of Human Movement, 2010)
The purpose of this work is to study the goalkeeper behavior and movement precue during the approaching race of the shooter to the ball, and compare professional (1ª y 2ª Division) and amateur (3ª Division) precue movement. Six professional goalkeepers (29.66+3.5 age) and 6 amateur goalkeepers (23.16+3.7 age) part in this study. The goalkeepers movement were filmed during 40 shoots, 20 from right shooter and 20 from left shooter, with a digital video camara. We applied a descriptive sectional design to analysed the subjets, and comparative sectional design to compared professional and amaterus goalkeepers. We identify two precues movementen to the left or right, by means of cinematic techniques applied: A knee extensión higher than 150º determine a movements towards the other part of the body. A knee flexion higher than 100º determine a movement toward this part of the body. No exist significant differences among profesional and amateurs goalkeepers KEY WORDS: precues, penalty, soccer, training, motor control and learning